Intracellular HSP72 detection in HL60 cells using a flow cytometry system based on microfluidic analysis - E. Gottwald; B. Lahni; G. Lüdke; T. Preckel; C. Buhlmann (BioTechniques)
HSP72 is an important marker for various environmental stresses and diseases, and many researchers need to detect HSP72 levels in various cells. We have therefore developed an assay to monitor intracellular heat-shock protein 72 expression on a microfluidic Lab-on-a-chip platform. We established this method to detect HSP72 intracellularly by antibody staining with DNA counterstaining. The Lab-on-a-chip technology is simple and efficient when performing flow cytometric assays. By permeabilizing the cells for the delivery of antibodies, we were able to show HSP72 expression after 30 min heat-shock at 44°C and then at various post-incubation times at 37°C. We compared our method to a conventional flow cytometer and an enzyme immunoassay technique.